BEBERAPA CATATAN SEPUTAR TEKS DAN MELODI NYANYIAN JEMAAT - Branckly Picanussa (IAKN Ambon, 2019)
Along with the development of science and technology, every day there are always new compositions for congregational singing with various texts and melodies. This article would like to provide some notes regarding the text and melody of congregational song which should be paid attention to by congregational song composers.